2003
DOI: 10.1074/jbc.m305599200
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor CCAAT-binding Factor CBF/NF-Y Regulates the Proximal Promoter Activity in the Human α1(XI) Collagen Gene (COL11A1)

Abstract: We have characterized the proximal promoter region of the human COL11A1 gene. Transient transfection assays indicate that the segment from ؊199 to ؉1 is necessary for the activation of basal transcription. Electrophoretic mobility shift assays (EMSAs) demonstrated that the ATTGG sequence, within the ؊147 to ؊121 fragment, is critical to bind nuclear proteins in the proximal COL11A1 promoter. We demonstrated that the CCAAT binding factor (CBF/NF-Y) bound to this region using an interference assay with consensus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…A second transcription factor reported to interact with the Col11a1 promoter is CBF/NF-Y (Matsuo et al, 2003). This transcription factor binds to the Col11a1 promoter within the -147 to -121 region the and activates transcription of promoter (Matsuo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A second transcription factor reported to interact with the Col11a1 promoter is CBF/NF-Y (Matsuo et al, 2003). This transcription factor binds to the Col11a1 promoter within the -147 to -121 region the and activates transcription of promoter (Matsuo et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This transcription factor binds to the Col11a1 promoter within the -147 to -121 region the and activates transcription of promoter (Matsuo et al, 2003). At this time, there is no evidence to suggest that Lef1 could be activating the Col11a1 promoter indirectly through CBF/NF-Y.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All mutagenesis plasmids were digested with SacI and HindIII and re-cloned into the SacI/ HindIII site of pGL3-Basic vector. Construction of the dominant negative CBF-B/NF-YA was generated by RT-PCR as previously described (26,29).…”
Section: Methodsmentioning
confidence: 99%
“…Lee and Greenspan (25) suggested that the GAGA boxes in the promoter and the first exon of the COL5A1 gene affect the transcription. We have recently characterized the proximal promoter of the COL11A1 (26) and Col5a1 genes (27). In these studies, we demonstrated that the CCAAT binding factor, CBF/ NF-Y, bound to the CCAAT motif in the proximal promoter and is involved in activation of the genes.…”
mentioning
confidence: 99%